2019
DOI: 10.1016/s0140-6736(18)32817-4
|View full text |Cite|
|
Sign up to set email alerts
|

Gentamicin compared with ceftriaxone for the treatment of gonorrhoea (G-ToG): a randomised non-inferiority trial

Abstract: Summary Background Gonorrhoea is a common sexually transmitted infection for which ceftriaxone is the current first-line treatment, but antimicrobial resistance is emerging. The objective of this study was to assess the effectiveness of gentamicin as an alternative to ceftriaxone (both combined with azithromycin) for treatment of gonorrhoea. Methods G-ToG was a multicentre, parallel-group, pragmatic, randomised, non-inferiority trial comparing treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 22 publications
1
82
0
1
Order By: Relevance
“…Our analysis identified gentamicin as an effective alternative to current cephalosporins such as ceftriaxone and cefotaxime. This is in line with a recent report showing that combination therapy of gentamicin and azithromycin is highly effective against uncomplicated gonorrhea [71].. A more recent randomized non-inferiority trial concluded that gentamicin is effective in clearing genital gonorrhea, but less so for pharyngeal and rectal infections [72]. Gentamicin resistance in culture has not been reported in clinical isolates of gonorrhea [73], and little is known about gentamicin resistance in the clinic due to its limited use.…”
Section: Discussionsupporting
confidence: 75%
“…Our analysis identified gentamicin as an effective alternative to current cephalosporins such as ceftriaxone and cefotaxime. This is in line with a recent report showing that combination therapy of gentamicin and azithromycin is highly effective against uncomplicated gonorrhea [71].. A more recent randomized non-inferiority trial concluded that gentamicin is effective in clearing genital gonorrhea, but less so for pharyngeal and rectal infections [72]. Gentamicin resistance in culture has not been reported in clinical isolates of gonorrhea [73], and little is known about gentamicin resistance in the clinic due to its limited use.…”
Section: Discussionsupporting
confidence: 75%
“…The results by Rob et al contrast with a similar RCT by Ross et al [6] who also compared gentamicin 240 mg with ceftriaxone 500 mg, but combined these treatments with 1 g rather than 2 g of azithromycin. Ross et al reported a similarly high efficacy for extragenital infections in the ceftriaxone arm (97%; 242/250) but not in the gentamicin arm (86%; 189/221).…”
mentioning
confidence: 84%
“…50 A relatively low efficacy using the 1 g dose also occurred in a recent UK trial where, even when given in combination with gentamicin, it was associated with a 9% failure rate. 51 There are several factors that may affect the interpretation of data from older studies that evaluated the efficacy of azithromycin as a treatment for gonorrhoea. First, gonococcal culture was used to assess cure, which may have overestimated treatment efficacy because culture has a relatively low sensitivity compared with nucleic acid amplification tests (NAAT); more recent studies, which assessed cure using NAATs, have reported lower cure rates.…”
Section: Azithromycin As Monotherapymentioning
confidence: 99%
“…53 A recent large trial found only a limited association between the MICs in those who cleared and did not clear gonorrhoea, and selecting treatment based on pre-treatment MIC breakpoints was not useful in predicting treatment failure. 51 There is therefore a danger that a low MIC report may provide false reassurance to clinicians.…”
Section: Azithromycin As Monotherapymentioning
confidence: 99%
See 1 more Smart Citation